THE MISTIFICATION OF PURITANTS ISLAMIC LAW EPISTEMOLOGY IN PROFETIC SOCIAL SCIENCE PERSPECTIVE - Rohmanu, Abid (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2018)
This paper is intended to elaborate the anthropocentric paradigm in the study of Islamic law which is done for two reasons. The first is the increasing trend of theocentricism within various puritan communities. This trend rejects the contextualization of Islamic law and has the potential to produce radical movements in the name of religion. The second is that, Islamic law studies is still rarely associated with the issues of legal paradigms, even though they are considered as the foundation in the establishment of Islamic law. Thus, this paper is written as an attempt to make the prophetic social science paradigma an analytical tool for puritans’ Islamic law epistemology. This study reveals that the epistemological demystification is very important for the study of contemporary Islamic law. There are two steps in carrying out epistemological demystification: the first is the transformation of the basic structure of Islamic law. This transformation requires a shifting issue from theocentric to the anthropocentrism. The transformative theoanthropocentric paradigm as the basic legal structure has the capability to contextualize Islamic law which is not only relevant to the Muslim community, but also to the community as a whole. The second is the development of a theoretical framework. Concerning with this, Kuntowijoyo offers analytic-synthetic theories which accommodate a demystified vision as a link to a transformative theological foundation.